2019
DOI: 10.1021/acsomega.9b02071
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Ru/C-Catalyzed Depolymerization of the Polymeric Proanthocyanidin-Rich Fraction from Bark To Produce Oligomeric Proanthocyanidins with Antioxidant Activity

Abstract: A new method has been developed for the high-value utilization of larch bark, which is regarded as a low-value byproduct of the logging industry. Polymeric proanthocyanidins (PPCs) were extracted from the Larix gmelinii bark and depolymerized by catalytic hydrogenolysis, using ruthenium/carbon (Ru/C) as the catalyst. The method has been found that although the molecular weight of the depolymerized product was significantly lower, the basic structural units were not destroyed, and the product retained a condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Additionally, Xu et al (2009) studied the effect of pomegranate flower extract on hepatic fat accumulation in Zucker diabetic obese rats with severe fatty liver disease and highlighted the hypolipidemic effect of the isolated polyphenols. Yu et al (2014) found that pomegranate leaves (PGL) have a similar modulating effect on lipid metabolism. Pomegranate leaves and their major active components (ellagic acid, gallic acid, pyrogallic gallic acid, and tannic acid) showed the effect of inhibiting pancreatic lipase activity in vitro.…”
Section: Hypoglycemic and Lipid-lowering Activitymentioning
confidence: 99%
“…Additionally, Xu et al (2009) studied the effect of pomegranate flower extract on hepatic fat accumulation in Zucker diabetic obese rats with severe fatty liver disease and highlighted the hypolipidemic effect of the isolated polyphenols. Yu et al (2014) found that pomegranate leaves (PGL) have a similar modulating effect on lipid metabolism. Pomegranate leaves and their major active components (ellagic acid, gallic acid, pyrogallic gallic acid, and tannic acid) showed the effect of inhibiting pancreatic lipase activity in vitro.…”
Section: Hypoglycemic and Lipid-lowering Activitymentioning
confidence: 99%
“…Although several methods for depolymerization of PACs are described in the literature, only some of them are applicable in the agri-food industry. In a study published by Zhu et al [ 39 ], it was reported that ruthenium/carbon-catalyzed depolymerization of polymeric PACs from larch bark resulted in a valuable increase in terms of oligomeric PACs. Moreover, Zhang et al [ 40 ] have described an innovative method based on the steam explosion treatment of grape seeds aimed at depolymerizing polymeric PACs into oligomeric ones.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate 58 is a useful model compound for the α- O -4 linkage found in lignin; of the eight distinct C–O bonds present in this substrate, we found that the benzylic position could be selectively cleaved to reveal the two arene products 59 and 60 in 86 and 81% yields, respectively (Scheme c). Tannins are another class of naturally abundant aromatic biomolecules that may serve as useful feedstock molecules in the bioeconomy . Exposing polyoxygenated tannin (−)-epicatechin 61 to this protocol allowed for the recovery of product 62 upon employing KF as a base rather than KO t Bu.…”
Section: Applicationsmentioning
confidence: 99%